Predictive Value of Optic Nerve Sheath Diameter in Subarachnoid Hemorrhage: A Systematic Review and Meta-Analysis - Tjahyanto, Teddy; Suryakanto, Milani (Fakultas Kedokteran Universitas Pelita Harapan, 2024)
Introduction : Optic nerve sheath diameter (ONSD) is a promising non-invasive marker for elevated intracranial pressure (ICP), potentially aiding in the prognostication of subarachnoid hemorrhage (SAH) outcomes. This study aimed to evaluate the predictive value of ONSD for poor outcomes in SAH patients, defined by the Glasgow Outcome Scale (GOS). Methods : A systematic review and meta-analysis were conducted, including studies from 2010 to 2021 that examined the relationship between ONSD and outcomes in SAH patients. A total of 615 patients were analyzed, with mean ages ranging from 54.1 to 58.8 years, and a predominance of males (38.2%). SAH severity was stratified using the Hunt and Hess classification, ranging from Grade 1 to Grade 5. The QUADAS-2 tool assessed the risk of bias, and the GRADE framework evaluated evidence certainty. Results : The pooled analysis revealed moderate predictive accuracy for ONSD in determining poor outcomes, with a pooled proportion of 0.70 (95% CI: 0.61–0.78). Significant heterogeneity (I² = 77.4%, p = 0.004) was observed, likely due to variability in ONSD thresholds, measurement techniques, and timing. Funnel plot analysis suggested potential publication bias, although further statistical testing is needed. Conclusions : ONSD demonstrates potential as a non-invasive tool for predicting poor outcomes in SAH patients. However, significant heterogeneity and moderate accuracy highlight the need for standardization of ONSD thresholds and measurement protocols. Further multicenter studies are required to validate its clinical utility and integrate it into comprehensive prognostic models.